Characteristics of crime convenience: the case of corporate offenders - Gottschalk, Petter (Deviant behavior, 2025)
This article presents a review of the research addressing the seriousness of corporate crime and the convenience for corporate offenders. Insights from this review are important as detection and prevention of corporate crime is dependent on addressing convenience issues for offenders. The perspective in this article suggests that convenience is a matter of avoiding strain and pain, saving time and efforts, overcoming barriers where the fences are at their lowest to gain from business possibilities and to avoid business threats such as bankruptcy. The opportunity for deviance among corporate offenders is typically based on their high social status and their legitimate access to resources to do both the right things and the wrong things. The opportunity structure to conceal deviance consists of institutional deterioration, lack of oversight and guardianship, and sometimes also criminal market forces. This is a scoping review article to identify convenience characteristics of corporate offenses and corporate offenders. Insights